Heart failure in pregnant women with cardiac disease: data from the ROPAC. Issue 3 (29th November 2013) - Ruys, Titia P E; Roos-Hesselink, Jolien W; Hall, Roger; Subirana-Domènech, Maria T; Grando-Ting, Jennifer; Estensen, Mette; Crepaz, Roberto; Fesslova, Vlasta; Gurvitz, Michelle; De Backer, Julie; Johnson, Mark R; Pieper, Petronella G
Abstract : Objective: Heart failure (HF) is one of the most important complications in pregnant women with heart disease, causing maternal and fetal mortality and morbidity. Methods: This is an international observational registry of patients with structural heart disease during pregnancy. Sixty hospitals in 28 countries enrolled 1321 women between 2007 and 2011. Pregnant women with valvular heart disease, congenital heart disease, ischaemic heart disease, or cardiomyopathy could be included. Main outcome measures were onset and predictors of HF and maternal and fetal death. Results: In total, 173 (13.1%) of the 1321 patients developed HF, making HF the most common major cardiovascular complication during pregnancy. Baseline parameters associated with HF were New York Heart Association class ≥3, signs of HF, WHO category ≥3, cardiomyopathy or pulmonary hypertension. HF occurred at a median time of 31 weeks gestation (IQR 23–40) with the highest incidence at the end of the second trimester (34%) or peripartum (31%). Maternal mortality was higher in patients with HF (4.8% in patients with HF and 0.5% in those without HF p<0.001). Pre-eclampsia was strongly related to HF (OR 7.1, 95% CI 3.9 to 13.2, p<0.001). Fetal death and the incidence of preterm birth were higher in women with HF compared to women without HF (4.6% vs 1.2%, p=0.001; and 30% vs 13%, p=0.001). Conclusions: HF was the most common complication during pregnancy, and occurred typically at the end of the second trimester, or after birth. It was most common in women with cardiomyopathy or pulmonary hypertension and was strongly associated with pre-eclampsia and an adverse maternal and perinatal outcome.